Benzothiophene-flanked diketopyrrolopyrrole polymers: impact of isomeric frameworks on carrier mobilities. Issue 86 (2nd September 2016) - Huang, Jianyao; Liu, Xiaotong; Gao, Dong; Wei, Congyuan; Zhang, Weifeng; Yu, Gui
Abstract : The influence of isomeric backbones on field-effect properties in benzothiophene-flanked diketopyrrolopyrrole polymers was investigated. Abstract : Exploring new building blocks for solution-processable polymeric semiconductors has attracted much attention. We herein develop two isomeric benzothiophene-flanked diketopyrrolopyrrole polymers with different linkage positions and further systematically study the electronic structures, optical properties, and field-effect characteristics. Both polymers exhibit typical p-type transport characteristics with the highest mobility being up to 0.80 cm 2 V −1 s −1 . Our results suggest that the isomeric backbones for conjugated polymers greatly affect charge transport properties.